A temporal record of microplastic accumulation in sediment cores of the Great Lakes, North America, reflects macroeconomic and regional influences - Sara L. Belontz; Patricia L. Corcoran; Linda Kimpe; Paul A. Helm; Chris Marvin (Canadian Science Publishing, 2024)
Documented plastic pollution throughout the Laurentian Great Lakes system prompted investigation of microplastics (MPs) in sediment cores. We examined offshore sediment cores from Lake Huron (LH43) and Lake Ontario (403A) to understand temporal trends and changes in microplastic (MP) pollution in the size range 53 µm to 2 mm. MP abundances varied from 18.1 to 280.1 particles per g of dry weight sediment (N g−1 dw) in LH43, and 8.2-488.4 g−1 dw in core 403A. The 15 cm cores are equivalent to 56 years of accumulation in Lake Huron and 72 years of accumulation in Lake Ontario. Analysis of the two cores shows an increasing trend in MP accumulation from 1964 to 1989, which mirrors the global plastic production rate. Subsequent peaks and troughs in the MP abundance profiles reflect macroeconomic changes and regional controls. These results show how changing abundances of MPs in lake sediment cores can act as proxies for global perturbations in oil supply as well as national economic shifts.